Weathering Influence on Properties of Siltstones from Istria, Croatia - Martina Vivoda Prodan; Željko Arbanas (Advances in Materials Science and Engineering)
Slaking and weathering of weak rocks result in slope instability. Siltstones from flysch rock masses are highly susceptible to weathering, which causes rapid changes in the geotechnical properties and durability. This study investigated siltstone samples of different weathering grades from flysch rock masses from the Istria Peninsula, Croatia, and determined the effects of weathering on their engineering properties. Laboratory testing of siltstone samples of different weathering grades was conducted to determine the specific gravity, grain size distribution, Atterberg limits, and uniaxial compressive strength. The standardized slake durability index is not sufficient to classify the durability of weak rock masses such as siltstones. Therefore, the durability of siltstone samples of different weathering grades was quantified from the fragment size distribution after each of five slaking cycles. The tested samples were classified based on the disintegration ratio, and the modified disintegration ratio was used to determine potential long-term degradation of the tested samples. The results indicated that weathering has a significant influence on the plasticity, uniaxial compressive strength, and durability characteristics and thus affects the landslides and erosion processes in siltstones in the flysch zone of the Istria Peninsula.